Cyclic Peptide Extracts Derived From Pseudostellaria heterophylla Ameliorates COPD via Regulation of the TLR4/MyD88 Pathway Proteins - Feng Lu; Feng Lu; Han Yang; Si-ding Lin; Li Zhao; Chang Jiang; Zhi-bin Chen; Ying-ying Liu; Yong-jun Kan; Juan Hu; Juan Hu; Wen-sheng Pang (Frontiers Media S.A., 2020)
We have explored the method of extraction and purification of cyclic-peptide extract (CPE) from Pseudostellaria heterophylla (Miq.) Pax. (Taizishen, TZS), characterized the structure about cyclic-peptide compounds and investigated the biological activity of CPE attenuating chronic obstructive pulmonary disease (COPD) in rats. The CPE from TZS was obtained by ethyl acetate, petroleum ether, hot water extraction, and alcohol-precipitation. Cyclic-peptide structures were distinguished using ultra-high performance liquid chromatography-quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MS/MS). Rats were induced by solid combustibles smoke (SCS) for the COPD model, and the anti-COPD activity of CPE was detected using lung airway resistance and dynamic lung compliance, as well as pulmonary tissue hematoxylin and eosin (HE) staining. The relevant inflammatory cytokines were assayed by enzyme-linked immunosorbent assay (ELISA). CPE obtained from TZS contained 12 cyclic-peptide constituents; the purity was up to 92.94%. CPE (200, 400, or 500 mg/kg/day) was given to SCS-induced COPD model rats orally for 15 days. The results showed that in rats given CPE (400 mg/kg/day) there was a sharp fall in lung airway resistance but a rise in dynamic lung compliance. The image analysis of lung tissue sections suggested that CPE could decrease the degree of alveolar destruction (p <0.05), alleviate lung inflammation, increase alveolar space, and improve the infiltration of inflammatory cells. CPE was found to reduce the levels of TNF-α, but increase IL-10, adjusting multiple cytokines in rat serum; the TLR4 mRNA, MyD88 mRNA and AP-1 mRNA levels, the expressing levels of p-JNK, p-p38 and p-TAK1 protein were significantly down regulated in rat alveolar macrophages. CPE intervention could improve the pulmonary ventilation function on COPD rats, which may be related to its effect in inhibiting the abnormal activation of the TLR4-MyD88-JNK/p38 pathway. This is the first report that the CPE of TZS lessens the severity of COPD episodes. The new preparation process of CPEs implements the anticipated goal, which is to refine CPE and actualize quality control.